APPLICATION OF SOCIAL GUIDANCE FOR RECREATIONAL GROUP TYPES IN REDUCING CHILDREN'S ANXIETY LEVELS IN THE SPECIAL GUIDANCE FOR CLASS I CHILDREN IN KUTOARJO - Maulana Fatah Putrayanda; Ali Muhammad (Polteknik Ilmu Pemasyarakatan, 2021)
If humans who live freely can experience increased anxiety in their lives, what about children who live in Special Child Development Institutions who have limitations in their freedom to do various things. Children are experiencing a crisis, are at a crossroads, and are socializing with society, and a child is actually not only punished physically, but also psychologically punished. This study is to answer the question of how the application of social guidance type recreational groups for children in the implementation of the coaching process in LPKA Class I Kutoarjo. In every child's personality development activity, there is a relationship between one and another, the location of the recreational group type social guidance activity is a combination of group counseling carried out by counselors and guidance by guardians to each child in groups. The application of the recreational group type of social guidance method in reducing the level of anxiety in children in LPLB Class I Kutoarjo. Based on the research conducted by the author, the implementation of recreational group type social guidance is not only about the driving factors but also the inhibiting factors in its implementation.